A REVIEW OF THE: MECHANISM OF BIOFILM FORMATION AFFECTING MEDICAL DEVICES - Raheem, Haider Qassim (International Journal Multidisciplinary (IJMI), 2026)
Objective: Bacterial colonies that live in an exopolysaccharide matrix and adhere to foreign surfaces in a living creature make up the complex biofilm. In therapeutic settings, biofilm often results in nosocomial, persistent infections. Method: This review gives a short account of the ideas underpinning the composition of, production of, and drug-resistant illnesses attributable to biofilm and cutting-edge therapeutic ways to combat and treat biofilm. Results: Antibiotics are insufficient to treat infections caused by biofilm because the bacteria in the biofilm have become resistant to them. Novelty: The use of cutting-edge technologies to handle the challenges posed by biofilm is justified by the high incidence of infections caused by medical devices.